APPLICATION OF GPS TRACKER SYSTEM ON BUSCITY WITH SUPPORTING SENSORS BASED ON INTERNET OF THING - S.T. M.T., Sukenda; Rachman Kurniadi, Yusup (International Journal of Psychosocial Rehabilitation, 2020)
City buses are one of the modes of public transportation used by the public. In its use, city buses still have shortcomings, one of which is the uncertainty of the schedule of bus traffic to the available bus stops. This can cause prospective passengers who are at bus stops to get bored waiting for the bus and can even switch to other modes of transportation that are more flexible and utilize technology already in use. So that transportation can be estimated when the time of arrival. The lack of utilization of the GPS tracker system technology which is integrated with smartphones on city buses, makes the mode of transportation can lag behind other modes of transportation in conducting public services in driving. Therefore, the use of GPS tracker system technology should also be applied to city buses, so that potential passengers can estimate the arrival of the bus to the bus stop where they are waiting. This system was built using the Arduino Uno microcontroller which is equipped with a GPS module that serves to get coordinates, also equipped with an ultrasonic sensor that can calculate the number of passengers. The data is sent to the broker who will later be saved to the database through a web service. The data can be sent to the broker, by using one more module that is integrated into the microcontroller, the wifi module which bridges the communication between the microcontroller and the broker through the internet network. After that the application made on an android smartphone will display a map and the location existence of each available bus.